Configuración relacional que se establece entre el agresor y la víctima partiendo desde el Modelo Intergeneracional - Andrade Rivero, Marisol (2010)
This research takes as main theme the violence in the relationship starting from a systemic approach, specifically, violent relations in marriage from the vision system transgneracional, and how they are building patones own model of interaction. For efficiency in its theoretical and epistemological, this model is used to analyze the research topic of domestic violence.